2022
DOI: 10.21608/aimj.2022.97818.1585
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of Chia Seeds Crude Extract Nanoparticles on Mcf-7 Breast Cancer Cell Line

Abstract: Users have the right to read, download, copy, distribute, print, search, or link to the full texts of articles under the following conditions: Creative Commons Attribution-Share Alike 4.0 International Public License (CC BY-SA 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The anti-inflammatory and antioxidant activities of CSO could clarify its antiapoptotic impact, as exhibited by the mild caspase-3 immunoexpression in immobilized rats pre or post-restraint with CSO. Similarly, it concluded the beneficial antiapoptotic impact of the aqueous extract of chia seeds 93 .…”
Section: Discussionmentioning
confidence: 88%
“…The anti-inflammatory and antioxidant activities of CSO could clarify its antiapoptotic impact, as exhibited by the mild caspase-3 immunoexpression in immobilized rats pre or post-restraint with CSO. Similarly, it concluded the beneficial antiapoptotic impact of the aqueous extract of chia seeds 93 .…”
Section: Discussionmentioning
confidence: 88%
“…Cancer cell migration is one of the crucial steps of metastatic cascade (45). Shaer et al demonstrated the anti-migration potencial of Salvia hispanica extract prepared with PLGA-PEG coated nanoparticles system (47). In some studies, the inhibitory effect of Carthamus tinctorius on the migration of various cancer cells has been shown (3,48).…”
Section: Discussionmentioning
confidence: 99%
“…All that was needed to create nanostructures was spontaneous emulsification during lipid hydration. The effects of utilizing chia seeds or chia seeds given by nanoparticles (Poly(lactideco-glycolide)-Poly (ethylene glycol)nanoparticles) on breast cancer cell culture were compared by Shaer and Al-Abbas (2022). Compared to regular chia seeds, chia seed nanoparticles have a more cytotoxic effect, stop cell migration, and cause apoptosis in breast cancer cells.…”
Section: How Can Chia Seeds Be Used In the Food And Nutrition Industr...mentioning
confidence: 99%